Learning by observation and learning by doing in Down and Williams syndromes. Issue 5 (26th December 2017) - Foti, Francesca; Menghini, Deny; Alfieri, Paolo; Costanzo, Floriana; Mandolesi, Laura; Petrosini, Laura; Vicari, Stefano
Abstract: New skills may be learned by active experience (experiential learning or learning by doing) or by observation of others' experience (learning by observation). In general, learning by observation reduces the time and the attempts needed to learn complex actions and behaviors. The present research aimed to compare learning by observation and learning by doing in two clinical populations with different etiology of intellectual disability (ID), as individuals with Down syndrome (DS) and individuals with Williams syndrome (WS), with the hypothesis that specific profiles of learning may be found in each syndrome. To this end, we used a mixture of new and existing data to compare the performances of 24 individuals with DS, 24 individuals with WS and 24 typically developing children on computerized tasks of learning by observation or learning by doing. The main result was that the two groups with ID exhibited distinct patterns of learning by observation. Thus, individuals with DS were impaired in reproducing the previously observed visuo‐motor sequence, while they were as efficient as TD children in the experiential learning task. On the other hand, individuals with WS benefited from the observational training while they were severely impaired in detecting the visuo‐motor sequence in the experiential learning task (when presented first). The present findings reinforce the syndrome‐specific hypothesis and the view of ID as a variety of conditions in which some cognitive functions are more disrupted than others because of the differences in genetic profile and brain morphology and functionality. These findings have important implications for clinicians, who should take into account the genetic etiology of ID in developing learning programs for treatment and education. Abstract : This research was aimed at investigating learning by observation and learning by doing in individuals with Down syndrome (DS) and Williams syndrome (WS), in the hypothesis that specific profiles of learning may be found in each syndrome. The main result was that the two groups exhibited distinct patterns of learning. Individuals with DS were markedly impaired in learning by observation, but not in learning by doing. Conversely, individuals with WS benefited from observational training while they were impaired in learning by doing. Altogether, these findings reinforce the syndrome‐specific hypothesis and indicate that in order to develop efficient learning programs for treatment and education it is necessary to take into account the genetic etiology of intellectual disability. Indeed, while an observational training may exert beneficial effects on the acquisition of new skills in individuals with WS, such advantages are not expected in individuals with DS.